Fathers Matter: Enhancing Healthcare Experiences Among Fathers of Children With Developmental Disabilities - Ogourtsova, Tatiana; O'Donnell, Maureen E.; Chung, Derrick; Gavin, Frank; Bogossian, Aline; Majnemer, Annette (Frontiers in Rehabilitation Sciences, 2021)
Background: Being a parent of a child with a developmental disability (DD, e.g. cerebral palsy, autism) comes with great challenges and apprehensions. Mothers and fathers of children with DD are experiencing heightened levels of psychological distress, physical health problems, financial difficulties, social isolation, as well as struggles with respect to traditional parenting roles. In relation to the latter, fathers’ involvement in caregiving in today’s society is increasing and is highlighted by its importance and positive contribution to their child’s development. However, fathers of children with DD report feeling excluded and marginalized by health-care providers (HCPs) when arranging for and getting involved in health-care services for their children. Currently, there is limited evidence as to what factors influence those experiences. We aimed to explore barriers to and facilitators of positive and empowering healthcare experiences, from the perspectives of fathers of children with DD and HCPs. Methods: A mixed-method approach including quantitative (survey) and qualitative (semi-structured interview) strategies was used. Participants were fathers of children with DD and HCPs working in childhood disability. Data analysis consisted of using descriptive statistics and an inductive-thematic analysis of emergent themes. Results: Fathers (n=7) and HCPs (n=13, 6 disciplines) participated. Fathers indicated that while they were moderately to very much satisfied with their interactions with HCPs, they reported that HCPs were only sometimes attentive to them during interactions. Fathers also revealed that positive interactions with HCPs in relation to their child had multiple benefits. Several themes related to barriers and facilitators of optimal interactions and parent-professional relationships emerged. These included session-factors (time, attention), personal-factors (knowledge of condition, child and health-care system, acceptance versus denial, previous experiences, culture, stereotypes, pre-existing beliefs, stress levels, working schedule), and family dynamics. Participants offered several insights into the different strategies that can be implemented to promote optimal interactions between fathers and HCP. Conclusion: We identified several barriers, facilitators and improvement strategies for optimal interactions and enhanced parent-professional relationships from the perspectives of fathers and HCPs. These can be integrated by existing clinical settings in efforts to enhance current clinical practices and improve child- and parent-related outcomes.